Fibrinogen and Fibrin Protect Fibroblast Growth Factor-2 from Proteolytic Degradation - Sahni, Abha; Baker, Christopher A.; Sporn, Lee Ann; Francis, Charles W. (Thrombosis and Haemostasis, 2000)
We have recently reported that fibrinogen and fibrin bind to fibroblast growth factor-2 (FGF-2) and potentiate its ability to stimulate proliferation of endothelial cells. In the present report, we have investigated the potential of fibrinogen and fibrin to protect FGF-2 from proteolytic degradation. FGF-2 was incubated with trypsin or chymotrypsin in the presence or absence of fibrinogen or fibrin and proteolysis of FGF-2 was assessed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting. In the absence of fibrinogen there was progressive tryptic degradation of FGF-2, but in the presence of fibrinogen, FGF-2 was completely protected from trypsin with no evidence of degradation. The degree of protection was maximum at a molar ratio of FGF-2 to fibrinogen 1:2. Fibrinogen afforded similar protection from degradation by chymotrypsin. Polymerized fibrin provided partial protection of FGF-2 from tryptic degradation, with intact FGF-2 present for up to 360 min. Fibrin provided nearly complete protection from chymotrypsin. These observations indicate that binding of FGF-2 to fibrinogen or fibrin provides protection from proteolytic degradation, and this may modulate its cell proliferative activity.
Keywords: Fibrinogen; FGF-2; trypsin; proteolysis